1973
DOI: 10.1002/ajpa.1330390108
|View full text |Cite
|
Sign up to set email alerts
|

Norms of size and annual increments of six anatomical measures of the cranium in boys and girls from four to fifteen years of age

Abstract: Norms of size and annual increments of six cranial dimensions are presented. The sample consists of 20 boys and 23 girls observed longitudinally from 4 to 15 years of age. The reported measurements are corrected for magnification of distortion and represent actual size rather than a roentgenographic projection. The dimensions of the cranial vault are observed to be closer to the adult size at age four years than the dimension involving the cranial base. The cranial base dimension continues to grow until adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The development of the frontal sinus is a structural accommodation necessitated by the forward growth of the face. Sekiguchi et al (1973) also showed that the bone deposition at the glabella was responsible for cranial elongation during and after adolescence. Head length was influenced not only by the brain but also by frontal sinus morphology.…”
Section: Discussionmentioning
confidence: 93%
“…The development of the frontal sinus is a structural accommodation necessitated by the forward growth of the face. Sekiguchi et al (1973) also showed that the bone deposition at the glabella was responsible for cranial elongation during and after adolescence. Head length was influenced not only by the brain but also by frontal sinus morphology.…”
Section: Discussionmentioning
confidence: 93%
“…But up to now, clinical CT data have been insufficiently used for describing craniofacial growth trends in infancy and early childhood. Many studies concentrate on neurocranial development (Sekiguchi et al ; Delye et al, ; Hahn et al, ; Marcus et al, ) while numerous others are concerned with particular aspects of anatomy (Escaravage & Dutton, ; Licus et al, 2014; Pool et al, and citations therein; Stepanenko, ).…”
Section: Introductionmentioning
confidence: 99%
“…The orbital volume increases rapidly in the initial 3 years after birth 2. The medial and lateral orbital walls enlarge significantly in the first year2 and continue with remodelling until age 5–7 3 4. By 12 years, the orbital volume is near adult size.…”
Section: Introductionmentioning
confidence: 99%